Analyzing the environmental impact of fuel switching: Evidence from ARDL analysis for policy considerations - Mohd Shahidan Shaari; Noorazeela Zainol Abidin; Miguel Angel Esquivias; Mohd Juraij Abd Rani; Temitayo Blessing Majekodunmi; Amri Sulong (Sustainable Futures)
The rise in global temperatures, driven by increased CO2 levels, is a pressing concern. Developing nations like Malaysia face challenges in transitioning to cleaner energy due to resource constraints, making natural gas a crucial transitional solution. This study introduces the Fuel Switch Variable to analyze the impact of shifting fuel consumption patterns on CO2. Using data from 1980 to 2020 and the ARDL model, findings show that policies promoting natural gas over oil and coal reduce CO2 emissions, while economic and population growth increase emissions. Policymakers should incentivize fuel switching, enforce energy efficiency standards, and invest in new technologies.